To the nomenclature of two species of the genus Adomerus (Heteroptera: Cydnidae) - Aukema, Berend; Gapon, Dmitry; Heijerman, Theodoor (Zootaxa, 2021)
The study of the lectotype of Sehirus fuscipennis Horváth, 1899 showed that this specimen is conspecific with Canthophorus maculipes sensu Aukema & Constant, 2016 and Adomerus maculipes sensu Gapon, 2018. To promote stability of nomenclature, the neotype of Cydnus maculipes Mulsant et Rey 1852 is designated instead of the lost syntypes. The name Sehirus aeneus Walker, 1867 is placed in synonymy with Adomerus maculipes (Mulsant et Rey, 1852). The name Adomerus fuscipennis (Horváth, 1899), stat. resurr. is reinstated. Colouration of the hemelytra, the structure of the parameres and aedeagi of the holotype of S. aeneus Walker, 1867 (female), of a male of A. maculipes, being topotypic with the latter, and of the lectotype of S. fuscipennis Horváth, 1899 are compared with each other and with descriptions of the terminalia of both species, recently published by the second author based on material from different localities. A map of the distribution of both species is given according to the literature data and studied collection materials.